Chaperone complex formation of the transcription factor MalR involved in maltose utilization and amylolytic enzyme production in Aspergillus oryzae. Issue 5 (4th May 2018) - Konno, Yui; Suzuki, Kuta; Tanaka, Mizuki; Shintani, Takahiro; Gomi, Katsuya
Abstract: The Zn2 Cys6 -type transcription factor MalR controls the expression of maltose-utilizing ( MAL ) cluster genes and the production of amylolytic enzymes in Aspergillus oryzae . In the present study, we demonstrated that MalR formed a complex with Hsp70 and Hsp90 chaperones under non-inducing conditions similar to the yeast counterpart Mal63 and that the complex was released from the chaperone complex after the addition of the inducer maltose. The MalR protein was constitutively localized in the nucleus and mutation in both the putative nuclear localization signals (NLSs) located in the zinc finger motif and the C-terminal region resulted in the loss of nuclear localization. This result indicated the involvement of NSLs in the MalR nuclear localization. However, mutation in both NLSs did not affect the dissociation mode of the MalR-Hsp70/Hsp90 complex, suggesting that MalR activation induced by maltose can occur regardless of its intracellular localization. Abstract: : Model for the regulation of A. oryzae MalR by molecular chaperones. The figure is depicted based on the model of the yeast Mal63 (Ran et al., 2008).